The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1039/b209490h
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high activity catalysts for the Suzuki coupling of aryl chlorides: the importance of catalyst longevity

Abstract: The incorporation of a new pi-acidic, orthometallated phosphite ligand into a palladium pre-catalyst gives considerably enhanced catalyst longevity and thus extremely high activity in the Suzuki coupling of deactivated, activated and sterically hindered aryl chloride substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…1.3 Â 10 5 ). [105] Recently, Bedford et al have reported on the hydrolytic instability of these complexes under typical Suzuki conditions, although the mechanistic consequences of this observation are still unclear. [106] Arylamine-palladacycles [107,108] such as 6a, b have been studied also by Bedford and co-workers.…”
Section: Vittorio Farina ð3þmentioning
confidence: 98%
“…1.3 Â 10 5 ). [105] Recently, Bedford et al have reported on the hydrolytic instability of these complexes under typical Suzuki conditions, although the mechanistic consequences of this observation are still unclear. [106] Arylamine-palladacycles [107,108] such as 6a, b have been studied also by Bedford and co-workers.…”
Section: Vittorio Farina ð3þmentioning
confidence: 98%
“…38 Interestingly, palladacycle 23b, which is structurally related to 23a, but in which the two non-ortho-metalated aryloxide substituents are replaced by a single salicylate residue, showed in the presence of PCy 3 extremely high activity in the Suzuki cross-coupling of deactivated, activated and sterically hindered aryl chlorides. 39 In 14,44 In 1997, Shen 45 established that a bulky and electron-rich phosphine, PCy 3 , is an effective Pd catalyst ligand for the cross-coupling of phenylboronic acid with aryl chlorides bearing electron-withdrawing groups (Scheme 3).…”
Section: Figure 2amentioning
confidence: 99%
“…As a consequence, in the last decade the progress on ligand chemistry became a major goal in the community of the organic chemist, and creativity partnered with a better understanding of the mechanistic necessities led to the emergence of several families of useful ligands for high-turnover palladium catalytic systems. For instance, and nonexhaustively: bulky electron-rich trialkylmonophosphanes, [9] (biaryl)dialkylphosphanes, [10] di-and tridentate pincers, [11] heterostructures at the origin of various palladacycles, [12,13] carbenes, [14] or multidentate polyphosphanes (Scheme 2) were found to be very efficient catalytic auxiliaries. [15] On this basis and ongoing since the mid 1990s we developed the design, synthesis, and characterization of original di-, tri-, and tetraphosphanes built on the ferrocenyl backbone (some representative examples of the library of ligands developed are depicted in Scheme 3).…”
Section: Introduction and Scopementioning
confidence: 99%
“…[13] The difficulties encountered in the coupling of halides other than iodides has often been ascribed to their reluctance to perform the oxidative addition to palladium. Improved catalytic activities were detected from systems that combine palladium to hindered strongly σ-electron-donating ligands (such as trialkylphosphanes); in addition, the success of bulky ligands has been suggested to be derived from the ability of these ligands to promote geometrically driven coordinative unsaturation important to the transmetalation and reductive elimination steps.…”
Section: Introduction and Scopementioning
confidence: 99%
See 1 more Smart Citation